Pengaruh Pendapatan Nelayan terhadap Pemenuhan Kebutuhan Pendidikan Anak di Wilayah Pesisir Desa - Rahmat M. Bidalo; Frahmawati Bumulo; Yulianti Tolarawe; Radia Hafid; Melizubaida Mahmud (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study examines fishermen's income's influence on fulfilling children's educational needs in the coastal area of Botubarani Village, Kabila Bone Sub-district, Bone Bolango Regency. This study employed a quantitative approach with a survey method. The sample consisted of 33 parents who work as fishermen. Data analysis employed a simple linear regression after performing a classical assumption test. The findings show that fishermen's income positively and significantly influences fulfilling children's educational needs. The higher the income of fishermen, the better the fulfillment of their children's educational needs. Furthermore, the findings show that fishermen's income contributes 39.5% to the fulfillment of children's educational needs. In contrast, the remaining 60.5% is influenced by others, such as government scholarship programs, the availability of affordable infrastructure and facilities, and children's learning motivation.